2022
DOI: 10.1590/1984-6398202218487
|View full text |Cite
|
Sign up to set email alerts
|

Do Flow, Enjoyment and Anxiety emerge equally in English Foreign Language Classrooms as in other Foreign Language Classrooms?

Abstract: The present study focused on differences in intensity of Foreign Language Enjoyment (FLE), Foreign Language Classroom Anxiety (FLCA), and proportion of time in a state of flow among 761 English FL learners and 825 FL learners of Languages Other Than English (LOTE). Participants in the LOTE group reported significantly higher levels of FLE and a higher proportion of class time in a state of flow, as well as lower levels of FLCA than the EFL group - although the effect size was very small. This suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
5
1
Order By: Relevance
“…The finding that LOTE learners reported significantly more enjoyment than EFL learners (albeit with a small effect size) confirms earlier research on frequency of flow in the classroom (Dewaele & MacIntyre, 2022). A closer look at the differences between the LOTE and the EFL groups for the three dimensions of FLE did not reveal striking disparities.…”
Section: Discussionsupporting
confidence: 84%
“…The finding that LOTE learners reported significantly more enjoyment than EFL learners (albeit with a small effect size) confirms earlier research on frequency of flow in the classroom (Dewaele & MacIntyre, 2022). A closer look at the differences between the LOTE and the EFL groups for the three dimensions of FLE did not reveal striking disparities.…”
Section: Discussionsupporting
confidence: 84%
“…Qualitative data also inform us that the teacher, not unexpectedly, is central to this process. Dewaele and MacIntyre (2022) had already researched to what extent the teacher is central to FLE and that teacher friendliness and encouraging approach are correlated to a higher level of FLE (Li et al, 2018: Dewaele et al, 2019Dewaele and MacIntyre, 2022). What is new in this study, and it is worth pointing out, is that the approach of the teachers is not merely based on their goodwill but on the strategic and planned decision to try a new approach (positive language education) and to implement PP interventions.…”
Section: Discussionmentioning
confidence: 82%
“…Analysis of descriptions of enjoyable episodes by participants in Dewaele and MacIntyre [21] showed that FLE was linked to specific classroom activities that allowed a degree of autonomy, peer recognition, a realization of progress, teacher recognition and teacher skills. In a follow-up study using the same database, Dewaele and MacIntyre [12] compared the proportion of time in a state of flow among EFL learners and FL learners of languages other than English (LOTE). LOTE learners reported spending a significantly higher proportion of class time in a state of flow than the EFL group, but the effect size was small.…”
Section: Learners' Emotions In Positive Psychologymentioning
confidence: 99%
“…The participants were then asked to rate their emotions (not included in the present study) and the time spent in a state of flow, both pre-pandemic in their in-person classes and in their ERT setting. They filled out items extracted from Larson and Csíkszentmihályi's [44] Experience Sampling Method and used in Dewaele and MacIntyre [12,13]. The items were preceded by the question: "What percentage of EFL class time does this apply to you (ranging from 0%-never to 100%-always)?…”
Section: The Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation